(untitled) (Bangladesh Critical Care Journal, 2017)
Background: Guillain-Barré syndrome is an acquired polyradiculo-neuropathy, often preceded by an antecedent event. It is a monophasic disease but a recurrence rate of 16 % is documented in a subset group of patients. Case presentation: Thirty-five-years-old female with past history of near complete recovery following Guillain-Barré syndrome 17 years back presented with acute, ascending symmetrical flaccid quadriparasis extending to bulbar muscles and respiratory compromise needing mechanical ventilation. Nerve conduction study revealed AMAN variant of Guillain-Barré syndrome. Cerebrospinal fluid analysis done after 1 weeks during recurrent episode revealed albuminocytologic dissociation. She was treated with intravenous immunoglobulin resulting in a remarkable recovery. Conclusion: Recurrence of Guillain-Barré syndrome can occur in a subset of patients with Guillain-Barré syndrome even after many years of asymptomatic period. Most patients with recurrent GBS respond favourably to treatment with plasmapheresis or IVIG. Bangladesh Crit Care J September 2017; 5(2): 135-138